PROFIL PEMERIKSAAN EVOKED POTENTIAL PADA KASUS NEUROONKOLOGI DI RSUPN DR. CIPTO MANGUNKUSUMO - Tejomukti, Teddy; Aninditha, Tiara (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2024)
ABSTRACT Introduction: Functional integrity of specified cortical areas and pathways in the central nervous system can be assessed by recording electrical potency such as Evoked Potential (EP) related to sensory or motoric events. Neoplasm can disturb functional integrity in the nervous system. Methods: This was an analytic cross-sectional research with the categorical approach in patients who underwent EP in Neurological Clinic RSUPN dr. Cipto Mangunkusumo Jakarta since 2022. Data were taken from medical records from December 2022 to March 2023. Demographic data, clinical data, neoplasm data, and EP examination data were recorded. The relation between neoplasm (type, location, number of lesions) and symptoms to EP results were analysed with Chi Square test Result: There were 660 evoked potential examinations consisting of 363 SSEP, 242 VEP and 55 BAEP examinations for various neurological clinical indications, however EP examinations indicated for neurooncology cases were 45 subjects or 6.8% of all examinations. A significant relation was found between sensory (p=0.03), motor (p=0.04), and autonomic (p=0.004) symptoms with abnormal SSEP examination results. Pain was not associated with abnormal SSEPs. No significant relationship was found between the number and location of tumors with the SSEP examination. All of the study subjects (100%) had visual disturbances and abnormal features of VEP. The BAEP examination was not analyzed because the sample size was too small. Conclusion: EP may be indicated in neurooncology cases in assessing functional lesions due to tumors, both intracranial and spinal. Keywords: Evoked Potential, nervous system neoplasm